2005
DOI: 10.1113/jphysiol.2004.078097
|View full text |Cite
|
Sign up to set email alerts
|

Calcium oscillations in interstitial cells of the rabbit urethra

Abstract: Measurements were made (using fast confocal microscopy) of intracellular Ca 2+ levels in fluo-4 loaded interstitial cells isolated from the rabbit urethra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
96
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 35 publications
15
96
0
Order By: Relevance
“…Simultaneous recordings of intracellular calcium and electrical activity in ICCs revealed that intracellular calcium oscillations in ICCs were synchronized with slow waves, which indicates the close relationship between the intracellular calcium oscillations and the pacemaker activities of ICCs (Liu et al, 2005a;Liu et al, 2005b). Similar activities were also observed in ICCs of murine stomach and rabbit urethra (Johnston et al, 2005). Moreover, the evidence which 1,2-bis (2-aminophenoxy) ethane-N,N,N',N'-tetraacetic acid acetoxymethyl ester (BAPTA-AM), an intracellular calcium chelator inhibited both pacemaker potentials and slow waves of murine intestine demonstrates the crucial role of intracellular calcium in the generation of pacemaker activities in ICCs (Kito et al, 2003).…”
Section: Intracellular Calcium Activitiessupporting
confidence: 50%
See 1 more Smart Citation
“…Simultaneous recordings of intracellular calcium and electrical activity in ICCs revealed that intracellular calcium oscillations in ICCs were synchronized with slow waves, which indicates the close relationship between the intracellular calcium oscillations and the pacemaker activities of ICCs (Liu et al, 2005a;Liu et al, 2005b). Similar activities were also observed in ICCs of murine stomach and rabbit urethra (Johnston et al, 2005). Moreover, the evidence which 1,2-bis (2-aminophenoxy) ethane-N,N,N',N'-tetraacetic acid acetoxymethyl ester (BAPTA-AM), an intracellular calcium chelator inhibited both pacemaker potentials and slow waves of murine intestine demonstrates the crucial role of intracellular calcium in the generation of pacemaker activities in ICCs (Kito et al, 2003).…”
Section: Intracellular Calcium Activitiessupporting
confidence: 50%
“…In the rabbit urethra ryanodine-operated calcium stores are considered to be prominent in the pacemaker activities in ICCs. The studies demonstrated that ryanodine abolished the intracellular calcium oscillations and pacemaker currents in ICCs from rabbit urethra, whereas 2-APB, an inhibitor of IP 3 receptor, partially but not completely inhibited the amplitude of the intracellular calcium oscillations (Johnston et al, 2005). Moreover, the calcium uptake by mitochondrion is also important for ICCs pacemaker activities in both gastrointestinal tract and urethra, because disruption of the mitochondiral membrane potential with the electron transport chain inhibitors rotenone and antimycin A and mitochondrial uncoupler carbonyl cyanide p-(trifluoromethoxy) phenylhydrazone (FCCP) and carbonyl cyanide m-chlorophenylhydrazone (CCCP) abolished both intracellular calcium oscillations and pacemaker currents in ICCs .…”
Section: Intracellular Calcium Activitiesmentioning
confidence: 99%
“…We have found that store depletion (CPA, thapsigargin), PLC inhibition (U73122) as well as blockade of IP 3 Rs abolished spontaneous Ca 2+ transients, indicating that the transients are due to release from cytoplasmic stores rather than Ca 2+ entry from extracellular space. Spontaneous cytosolic Ca 2+ elevations arising from the ER were previously described in many excitable and non-excitable isolated cell types, including neutrophils [31], myocytes [32,33], interstitial cells [34], astrocytes [35] and neurons [36]. However, in many of these cell preparations, spontaneous cytosolic calcium elevations occur at much higher frequencies, being rather oscillatory than stochastically distributed.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of recent papers, ICC-like cells have been claimed to occur in other organs: vas deferens [25], urethra [26][27][28], bladder [29][30][31][32][33], ureter [34,35], uterus [36,37], blood vessels [38][39][40], lymphatics [41], prostate [42,43], penis [44], mammary gland [45] and pancreas [46].…”
Section: Introductionmentioning
confidence: 99%